Accreting pulsating white dwarfs: Probing heating and rotation. Issue Volume 15:Issue S357(2019) (October 2019) - Szkody, Paula; Gänsicke, Boris; Toloza, Odette; Godon, Patrick; Sion, Edward; Kafka, Stella; Bell, Keaton; Vanderbosch, Zachary
Abstract: The white dwarfs in close, interacting binaries provide a natural laboratory for exploring the effects of heating and angular momentum from the accreting material arriving on the surface from the companion. This study is even more fruitful when it involves a pulsating white dwarf, which allows an exploration of the effects of the accretion on the interior as well as in the atmosphere. The last decade has seen the accomplishment of UV (HST) and optical (ground) studies of several accreting white dwarfs that have undergone a dwarf nova outburst that heated the white dwarf and subsequently returned to its quiescent temperature. The most recent study involves V386 Ser, which underwent its first known outburst in January 2019, after 19 years at quiescence. V386 Ser is unique in that its quiescent pulsation shows a triplet, with spacing indicating a rotation period of 4.8 days, extremely slow for accreting white dwarfs. This paper presents the result of HST ultraviolet spectra obtained 7 months after its outburst that shows the first clear confirmation of shorter period modes being driven following the heating from a dwarf nova outburst.